Gab2 is Essential for Transformation by FLT3-ITD in Acute Myeloid Leukemia. Issue 2 (April 2019) - Sies, Katharina; Spohr, Corinna; Gründer, Albert; Todorova, Rumyana; Uhl, Franziska Maria; Huber, Julia; Zeiser, Robert; Pahl, Heike Luise; Becker, Heiko; Aumann, Konrad; Brummer, Tilman; Halbach, Sebastian
Abstract : Supplemental Digital Content is available in the text